Perubahan Ekonomi dan Sosial Keagamaan Selama Pandemi Covid-19 Pada Masyarakat Pesisir Pulau Simardan - Windi Ramayanti; Nurhalija Sitompul; Rahmat Sulistio; Muhammad Eko Marpaung; Fatimah Zahara (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
This study examines the changes that occurred during the economic and socio-religious Covid-19 pandemic in coastal communities in Pulau Simardan Village, Datuk Bandar Timur District, Tanjungbalai City.  The research method applied in this research is survey method with descriptive qualitative research.  Data was collected by interview and observation using purposive sampling technique, namely selecting informants such as BKM Mosque, Kelurahan staff and neighborhood heads. Snowball sampling technique was selecting respondents who were interviewed about changes in economic income and socio-religious interactions during the pandemic.  This study aims to obtain information about the changes that occurred during the Covid pandemic from an economic and socio-religious perspective in coastal communities.  The findings of the decline in income during the pandemic were motivated by a decrease in income, resulting in reduced people's purchasing power and difficulties in marketing goods with the implementation of the PSBB.  While socio-religious changes are sought for all activities from home and some religious activities are limited, such as regular recitation of mosque youth and morning cult studies at the Nurul Jalal Mosque.